Thorough morphological and genetic evidence confirm the existence of the endemic honey bee of the Maltese Islands Apis mellifera ruttneri: recommendations for conservation. Issue 5 (20th October 2017) - Zammit-Mangion, Marion; Meixner, Marina; Mifsud, David; Sammut, Sheryl; Camilleri, Liberato
Abstract : The status of Apis mellifera ruttneri, an endemic honey bee of the Maltese islands, was uncertain after a series of devastating Varroa mite infestations followed by ill-conceived replacement programs. Morphometric analysis, which was the method originally used to identify this honey bee subspecies, was carried out using 33 different parameters . Thirty-two colonies exhibiting morphometric data that corresponded to those in the original description of A. m. ruttneri were identified ( p  > 0.99). In addition, the mitochondrial DNA region spanning the tRNA leu -Cox2 region from colonies bearing the morphometric data associated with A. m. ruttneri was amplified (77% showed the P0 QQ structure). The data presented confirm morphometric similarity with A. m. siciliana and A. m. intermissa . We report the presence of A4, A8 and A9 haplotypes in A. m. ruttneri (83%; frequency 0.189, 0.081 and 0.486 respectively). European haplotypes belonging to the C1, C2 and M7 haplotypes were also recorded (17%; 0.135, 0.081, 0027). Recommendations for the conservation of this honey bee are proposed.